Structural and productive responses of signalgrass and its association with leaf area index and light interception under silvopastoral or monoculture systems - Diego de Lima Coêlho; Alexandre Carneiro Leão de Mello; José Carlos Batista Dubeux Jr.; Márcio Vieira da Cunha; Mércia Virginia Ferreira dos Santos; Erinaldo Viana deFreitas; André Pereira Freire Ferraz; Amanda Maria Gallindo dos Santos; Janerson José Coelho; Igor Lima Bretas (Agrosystems, Geosciences & Environment)
Abstract Silvopastoral systems (SPSs) have emerged as one of the most prominent alternatives for grassland recovery. We evaluated the structural and productive responses of signalgrass [Urochloa decumbens (Stapf.) R. D. Webster] and its association with leaf area index (LAI) and light interception (LI) measured with different equipment across different cultivation systems. The treatments consisted of monoculture signalgrass (MS), SPS established with signalgrass and the arboreal legume gliricidia [Gliricidia sepium (Jacq.) Steud.] (SG), and SPS established with signalgrass and the arboreal legume sabiá (Mimosa caesalpiniifolia Benth) (SS) in a randomized complete block design with three replications. Average height, compressed height, herbage mass (HM), herbage mass density, LAI, and LI, % of the signalgrass canopy were evaluated every 28 days from September 2014 to August 2015. Greater HM was found in MS (p ≤ 0.05), and the lowest values were observed in SS for both seasons (2.376, 1.721, and 813 kg DM ha−1 for MS, SG, and SS, respectively). The correlations between canopy height and LAI or LI generally ranged from nonexistent to weakly positive, regardless of the treatment, equipment used, and season. The structural and productive responses of signalgrass and the correlations between the variables studied vary throughout the year in response to climate variation and the cultivation system. SPSs with gliricidia or sabiá trees reduce signalgrass HM, with a greater magnitude in systems with sabiá. Canopy height and HM are unreliable indicators of the critical LAI (95% LI) to guide grazing management in the evaluated systems.